Cortical reorganization correlates with motor recovery after low-frequency repetitive transcranial magnetic stimulation combined with occupational therapy in chronic subcortical stroke patients - Satoshi Katai; Masanori Maeda; Sumie Katsuyama; Yoichi Maruyama; Maiko Midorikawa; Toshiki Okushima; Kunihiro Yoshida (NeuroImage: Reports)
The combination of low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) and intensive occupational therapy (iOT) has been shown to ameliorate upper limb hemiparesis in patients with chronic subcortical stroke. However, the neural mechanisms underlying its efficacy are poorly understood. Our aim was to examine the cortical reorganization after LF-rTMS and iOT, as well as to explore its association with the degree of motor recovery using functional magnetic resonance imaging (fMRI). Thirty chronic subcortical stroke patients with mild-to-moderate upper limb hemiparesis underwent 18 treatment sessions. Each session included LF-rTMS to the unaffected hemisphere for 20 min as well as iOT for 120 min. The patients were evaluated before and after therapy using behavioral assessments, including the Fugl-Meyer Assessment (FMA), Wolf Motor Function Test (WMFT), and task-based fMRI. The fMRI data obtained during hand movement were used to calculate the laterality index (LI). After the treatment, the motor function test scores of FMA and WMFT improved significantly. The LI during movements of the affected hand increased significantly, suggesting changes in the activation balance within the primary motor, primary sensory, and premotor cortexes toward the lesioned hemisphere. Moreover, the LI changes in the aforementioned areas significantly correlated with gains in the WMFT. These results suggest that the motor improvements produced by the combination of LF-rTMS and iOT in chronic subcortical stroke patients are closely linked to cortical reorganization, in which a more physiological activation pattern is reinstated in the ipsilesional hemisphere by suppression of the aberrant activation of the contralesional hemisphere.